(1)f/(x)=(ax+a-x)lna,
若0<a<1,则<0,lna<0,所以f/(x)>0;
若a>1,则>0,lna>0,所以f/(x)>0,
因此,任意a>0且a≠1,都有f/(x)>0,f(x)在(-∞,+∞)上的单调递增.
(2)直接计算知f(1)-1=0,f(2)-2=a+a-1-2,f(3)-3=a2+a-2-2,
根据基本不等式a+a-1-2>0,所以f(2)-2>f(1)-1,
又因为(a2+a-2-2)-(a+a-1-2)=[(a+a-1)2-(-)2]=(-)2(a+a-1+1)=(a-1)2(a+a-1+1)>0,
所以f(3)-3>f(2)-2.
假设∀x>0,f(x+1)-(x+1)>f(x)-x.
记g(x)=[f(x+1)-(x+1)]-[f(x)-x][(ax+1-a-x-1)-(ax-a-x)]-1=-1,g/(x)=lna.与(1)类似地讨论知,对∀x>0和∀a>0且a≠1都有g/(x)>0,g(x)在[0,+∞)上的单调递增,g(0)=0,
所以g(x)>g(0)=0,即∀x>0,f(x+1)-(x+1)>f(x)-x.
(3)=1,=(a+a-1),=,
根据基本不等式=(a+a-1)>1=,->-[]2=>0,
所以>>.
假设∀x>0,>.
记g(x)=,x>0,g/(x)=×x(ax+a-x)lna-(ax-a-x) |
a2-1 |
,
设h(x)=x(ax+a-x)lna-(ax-a-x) |
a2-1 |
,
则h(0)=0且h/(x)=,
类似(1)的讨论知h/(x)=>0,
从而h(x)>h(0)=0,g/(x)>0,g(x)在R+上单调增加,
所以∀x>0,>.